Perilaku Konsumsi Mie Instan Pada Remaja - Wiwin Efrizal (Ilmiah Institut Citra Internasional, 2021)
Instant noodles as a practical food, easy to serve, delicious, many choices of flavors and low prices are very popular with various groups, including teenagers. Even so, excessive consumption of instant noodles can cause health hazards. The author wants to know the behavior of adolescents in Bangka Belitung in consuming instant noodles. The research used quantitative using a questionnaire method at the end of August 2020 to 45 respondents randomly and the data obtained were analyzed descriptively and graphically. In this study, it was found that the behavior of consuming instant noodles was carried out by 84.4% of respondents at elementary school age with a percentage of 71.1% consuming 1-3 packs per week. Other behavior when processing / serving it as much as 51.1% of respondents think they like adding spices / other food ingredients to increase taste / taste and nutritional intake.